ANALISIS NOM DAN BOPO TERHADAP PROFITABILITAS BANK SYARIAH INDONESIA DI ERA PANDEMI COVID 19 (Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of this study is to analyze the effect of NOM and BOPO on the profitability of Islamic banks in Indonesia and at the same time analyze the impact of covid-19 as a moderating variable. The analysis tool to fulfill the goodness of fit model uses the classical assumption test including the normality test; multicollinearity test; heteroscedasticity test; autocorrelation test; and linearity test. Path analysis to test direct and indirect relationships, moderating regression analysis (MRA), and hypothesis testing. The population and sample in this study were 13 Islamic banking companies listed on the Indonesia Stock Exchange. The results of the study are that the NOM and BOPO variables affect ROA at Islamic Commercial Banks in Indonesia in 2018-2020 which means that Islamic banks are able to obtain net operations so that the average ability of productive assets to generate profits is known. The Covid'19 pandemic variable as a moderating variable strengthens the influence of NOM and BOPO on ROA